Islamic psychology - Al' Mahd, Muhammad, Dr. (Kuala Lumpur : Saba Islamic Media, 2004)
A presentation of a much needed truly Islamic psychology which could be incorporated into the pratice of Muslim psychologist, regardless of their particular methodology. Plus, a detail explanation of how Western secular materialistic psychology had wrong intentions from the begining and why it proved to be so completely unsuccessful.
Presenter: Muhammad Al' Mahd
Keywords: Islam; Psychology